Costs of growing timber trees in agroforestry systems with coffee in Costa Rica - Murillo-Gamboa, Olman (2023)
Introduction. The lack of economic information is a barrier to the promotion of agroforestry systems (AFS). The forestry component could represent an important contribution to economy, an increase in biodiversity and, a high carbon footprint in coffee AFS, which are promoted throughout more than 93 600 ha in 8 regions of Costa Rica. A new coffee-timber production relationship model is required, which would provide additional economic value to the coffee growers, than the traditional environmental services. Objective. To determine the costs required for cropping timber trees in a coffee plantation. Materials and methods. A complete cost structure of shading-trees cultivation in coffee plantations is reported. It is based on an individual tree model due to its greater applicability. The cost model is based on the cultivation of a maximum of 275 trees.ha-1 (6 x6 m in an irregular distribution), which allows a thinning of 50% of the trees in year 7, for the cultivation of laurel (Cordia alliodora) and cedro (Cedrela odorata) trees mainly, at altitudes between 700 and 1450 meters above sea level. Results. Production costs of a timber tree up to year 15 is ¢2386.tree-1 (US$4, exchange rate of ¢600), where 50% corresponds to labor work, 24% to management and technical assistance, 15% to fertilizers and other inputs and 11% for the trees. Laurel tree intercepts 60% of solar radiation with no effect in the production of 36.5 bushels.ha-1 in ovatá coffee variety at 1200 masl. Conclusions. The total costs of planting 275 trees.ha-1 in AFS with coffee is ¢2386.tree-1 (US$3.98). A financing scenario could make a capital contribution of ¢950 per tree in year 0, another capital contribution of ¢850 in year 5, for a total of ¢1750.tree-1 ($2.9). However, FONAFIFO’s current financing model for coffee production in AFS could keep its capital contribution scheme in the first five years and same amount of ¢2000 per tree, in order to avoid volatility in agrochemicals prices. The cultivation of timber shade trees in coffee is low and would have a high economic, social and environmental impact on coffee farming in Costa Rica.